2019
DOI: 10.1111/jfbc.13124
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and biological investigations on twoNepetaspecies:Nepeta heliotropifoliaandN. congestasubsp.cryptantha

Abstract: In the present study, the essential oil and aroma compositions of Nepeta heliotropifolia (NH) and N. congesta subsp. cryptantha (NC) were determined by gas chromatography-mass spectrometry (GC-MS) and gas chromatography-flame ionization detector (GC/FID), and their phenolic compounds by liquid chromatography-tandem mass spectrometry (LC-MS/MS). In addition, antioxidant, cytotoxic, anticholinesterase, urease, and tyrosinase activities of essential oils obtained from NH and NC aerial parts and ethanol extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
2
13
3
Order By: Relevance
“…Results revealed that the flower extracts were found to contain higher amount of phenolic compounds and the major compound was indicated as rosmarinic acid (8,909.91 and 4,317.20 mu g/g for NHE and NCC, respectively). Similar to our results, flower extracts of the Nepeta species exhibited strong antioxidant activity in DPPH and ABTS radical scavenging assays [4]. To the HPLC/MS/MS analysis results; rutin, ferulic acid, and chrysophanol were the significant compounds in N. fissa extracts [10].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Results revealed that the flower extracts were found to contain higher amount of phenolic compounds and the major compound was indicated as rosmarinic acid (8,909.91 and 4,317.20 mu g/g for NHE and NCC, respectively). Similar to our results, flower extracts of the Nepeta species exhibited strong antioxidant activity in DPPH and ABTS radical scavenging assays [4]. To the HPLC/MS/MS analysis results; rutin, ferulic acid, and chrysophanol were the significant compounds in N. fissa extracts [10].…”
Section: Discussionsupporting
confidence: 85%
“…Nepeta species are widely used in traditional medicine for their expectorant, diuretic, antispasmodic and antiasthmatic activities, so that the local people mostly benefit from the Nepeta species as spasmolytic, diuretic and bronchodilator agents. Terpenes, flavonoids, phenolic acids, iridoids and essential oil have been reported, and especially terpenoids and flavonoids are the dominant constituents within the genus Nepeta [1,[3][4][5].…”
mentioning
confidence: 99%
“…Essential oils were obtained using a Clevenger apparatus from the dried aerial parts of the mentioned Salvia taxa (100 g) which were crumbled into small pieces in distilled water (500 mL) for 3 h. The obtained essential oils were dried over anhydrous Na 2 SO 4 and stored at + 4 °C before analyses, and then the essential oil samples were diluted with hexane (1 : 3 v/v) prior to GC/MS and GC/FID analyses. [30] The dried aerial parts of S. cerino-pruinosa var. cerino-pruinosa, S. cerino-pruinosa var.…”
Section: Discussionmentioning
confidence: 99%
“…Components of essential oils (from shadow-dried aerial parts of the species) obtained by hydrodistillation method using Clevenger apparatus were determined by GC-FID. [30] HP-5MS UI capillary column (30 m-0.25 mm and 0.25 μm film thickness) was used. The injector temperature was adjusted at 250 °C.…”
Section: Gc-fid and Gc/ms/head Space Conditions For Essential Oil And Aroma Analysesmentioning
confidence: 99%
“…Nepeta are used diuretic, anti-spasmodic, antiasthmatic (Goldansaz et al, 2019;Kaska et al, 2019), expectorant, cough suppressant (Sharma et al, 2021), sedative, antiseptic (Sarikurkcu et al, 2019), antipyretic, antiallergy (Ashrafi et al, 2020) and as a muscle relaxant (Akdeniz et al, 2020). Besides, it also has many biological activities such as antioxidant (Azizian et al, 2021), antibacterial, antiinflammatory (Kaska et al, 2019;Sitarek et al, 2020), anticancer, antiparasitic (Ashrafi et al, 2020), antiplatelet, antiangiogenesis (Al-Sheddi et al, 2018), antimicrobial, antiviral (Sharma and Cannoo, 2013;Afshar et al, 2017), antifungal, insecticide (Süntar et al, 2018;Sharma et al, 2021), cytotoxic, phytotoxic (Formisano et al, 2011), genotoxic, apoptotic (Süntar et al, 2018), antitumor, larvicide, analgesic, antidepressant and anticonvulsant (Süntar et al, 2018;Akdeniz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%